Expanding the clinicopathological spectrum of succinate dehydrogenase-deficient renal cell carcinoma with a focus on variant morphologies: a study of 62 new tumors in 59 patients - Fuchs, Talia L.; Maclean, Fiona; Turchini, John; Vargas, A. Cristina; Bhattarai, Selina; Agaimy, Abbas; Hartmann, Arndt; Kao, Chia-Sui; Ellis, Carla; Bonert, Michael; Leroy, Xavier; Kunju, Lakshmi P.; et al. (Modern Pathology, 2021)
Most succinate dehydrogenase (SDH)-deficient renal cell carcinomas (RCCs) demonstrate stereotypical morphology characterized by bland eosinophilic cells with frequent intracytoplasmic inclusions. However, variant morphologic features have been increasingly recognized. We therefore sought to investigate the incidence and characteristics of SDH-deficient RCC with variant morphologies. We studied a multi-institutional cohort of 62 new SDH-deficient RCCs from 59 patients. The median age at presentation was 39 years (range 19-80), with a slight male predominance (M:F = 1.6:1). A relevant family history was reported in 9 patients (15%). Multifocal or bilateral tumors were identified radiologically in 5 patients (8%). Typical morphology was present at least focally in 59 tumors (95%). Variant morphologies were seen in 13 (21%) and included high-grade nuclear features and various combinations of papillary, solid, and tubular architecture. Necrosis was present in 13 tumors, 7 of which showed variant morphology. All 62 tumors demonstrated loss of SDHB expression by immunohistochemistry. None showed loss of SDHA expression. Germline SDH mutations were reported in all 18 patients for whom the results of testing were known. Among patients for whom follow-up data was available, metastatic disease was reported in 9 cases, 8 of whom had necrosis and/or variant morphology in their primary tumor. Three patients died of disease. In conclusion, variant morphologies and high-grade nuclear features occur in a subset of SDH-deficient RCCs and are associated with more aggressive behavior. We therefore recommend grading all SDH-deficient RCCs and emphasize the need for a low threshold for performing SDHB immunohistochemistry in any difficult to classify renal tumor, particularly if occurring at a younger age.
CRIS-Team WoS Importer:2021-12-31